Effect of practice on learning a balance task in children, adolescents, and young adults - Muehlbauer, Thomas; Brueckner, Dennis; Schedler, Simon (Frontiers in Psychology, 2022)
Background: A lower developmental stage of the postural control system in childhood compared to adolescence and adulthood has been reported in numerous studies and suggests differences (i.e., less improvements in children than in adolescents and young adults due to the immature postural control system) during learning a balance task. Therefore, the present study examined the effect practice on learning (i.e., retention and transfer) a balance task in healthy children, adolescents, and young adults. Methods: Healthy children (n=32, 8.5 ± 0.5 years), adolescents (n=30, 14.6 ± 0.6 years), and young adults (n=28, 24.3 ± 3.3 years) practiced balancing on a stabilometer (i.e., to keep the platform as close to horizontal as possible) for two days. On the third day, learning was assessed using a retention (i.e., balance task only) and a transfer (i.e., balance task plus concurrent motor interference task) test. The root-mean-square-error (RMSE) was calculated and used as outcome measures. Results: Over the course of practice, significant improvements (i.e., reduced RMSE; p < .001) were detected in favor of children and young adults. However, neither the retention nor the transfer test showed significant group differences. Conclusion: Our findings indicate that learning a balance task did not seem to be influenced by the developmental stage of the postural control system.